Aplikasi Ekstrak Gel Lidah Buaya Dan Kulit Manggis Sebagai Inovasi Alternatif Disclosing Solution Herbal Pendeteksi Plak Gigi Sebagai Indikator Kebersihan Gigi Dan Mulut Dalam Usaha Promotiv Dan Preventif - Kai, Meggy; Rahmawati, Ida; Sari, Emilda (UPPM Poltekkes Kemenkes Banjarmasin, 2025)
Based on the 2018 Basic Health Research (Riskesdas), 61.9% of Indonesians aged 55–64 years and 54.2% aged over 65 years experienced dental and oral health problems, while in South Kalimantan the prevalence reached 59%. Among children aged 10–14 years, only 2.1% brushed their teeth properly, and overall only 8.1% of Indonesians practiced correct and timely toothbrushing habits. Poor oral hygiene is strongly influenced by behavioral factors, particularly the lack of awareness regarding the importance of maintaining dental and oral health. This community service project was conducted at SDN Tambak Raya Martapura, targeting 47 elementary school students from grades I to VI, with the aim of improving oral hygiene through promotive and preventive approaches. A total sampling technique was applied, and interventions included mass toothbrushing, health education, and the application of disclosing solution to detect dental plaque as an indicator of oral hygiene. Initial examinations showed that the majority of students had moderate levels of oral hygiene. After the intervention, follow-up examinations demonstrated significant improvements, with 32 students (76%) achieving good oral hygiene, while 10 students (24%) remained in the moderate category. No students were found in the poor category. The targeted outcomes were successfully achieved, indicating that the combination of mass toothbrushing and disclosing solution application was effective in promoting oral health. It is recommended that schools, parents, and health workers continue to integrate these activities regularly to improve children’s oral hygiene and prevent future dental health problems.